PERANCANGAN SISTEM INFORMASI GEOGRAFIS ONLINE (SIG-ONLINE) DALAM PENGUATAN POTENSI GAMPONG - Muhammad Isa; Freddy Sapta Wirandha; Didik Sugiyanto; Elin Yusibani (LPPM Universitas Bina Bangsa, 2023)
An Online Geographic Information System (SIG-Online) has been successfully designed to strengthen the potential of gampong (village) as a form of community service at Gampong Meunasah Mesjid Lampuuk. The problem of partners so far is the lack of information about the importance of Gampong potential so that partners experience limitations in knowing access to information about the potential of the gampong. The stages in building a GIS Online system begin with planning, analysis, design, implementation and maintenance. SIG-Online will later display Gampong potential data and Gampong information equipped with geospatial data such as satellite image basemaps of the Gampong area, Gampong boundaries, gampong layout and population data of the Gampong community and its natural beauty. Technical stages in building SIG-Online start from data collection, processing, digital analysis and displaying SIG-Online on android applications by utilizing the internet network. In the process of building SIG-Online, community service collaborates with the non-governmental organization (NGO) Prodeelat. The output of this service is to provide convenience for partners in accessing the potential of gampong through the SIG-Online system so that there is an increase in peace and welfare in the community (village).